Conflictology and the Law «On Mediation» - Symbat Ye. Shakirov, Shakirov; Асан А., Амангельдиев (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
Modern realities in a rapidly changing world are condensing events with conflict potential, which will certainly affect the prospects for the further development of mankind as a whole, as well as in relation to individual states and social groups. Such phenomena as social disunity, racial and ethnic intolerance, terror, often resulting in dramatic social and interethnic conflicts, actualize the need to develop the institution of mediation. In October 2021, at a meeting of the Assembly of the People of Kazakhstan, President Kassym-Jomart Tokayev noted «It is necessary to actively use the capabilities of public legal institutions, in particular, mediation». As the next priority task, the Head of State noted «that for ethnomediation in our conditions the format of professional negotiators is the most effective».The January events of last year exposed a number of social problems, including the gap between the poor and the rich. In his speech, the Head of State emphasized that «the country has changed, and the attitude of Kazakhstan to power, the economic system and life in general has also changed. And now there is a strategic task of a deep transformation of the entire social structure. In the discourses of modern foreign and domestic experts, questions about the problems of world development through the escalation of social conflicts are more often raised. Based on this, we consider it important that real reforms should contribute to meeting the security interests of modern Kazakhstan. This requires further formation and systematization of the institution of mediation in the socio-cultural life of Kazakhstan.